2021
DOI: 10.1016/j.buildenv.2020.107362
|View full text |Cite
|
Sign up to set email alerts
|

An optimal dimensioning method of a green wall structure for noise pollution reduction

Abstract: This paper concern the optimization of a multilayered green wall structure including substrate and foliage in order to reduce as much as possible backward noise reection and forward transmission from the wall. Each component involved in the wall structure is fully characterized experimentally to get its tranfer matrix. Simulation demonstrated that foliage layer superimposed to substrate layer doesn't aect the transmission losses but contributes greatly to the increase of return losses of the green wall structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…There are several nomenclatures to explain biowall terminology and these include vertical gardens [5], active living walls [6], and green walls [7,8,9,10,11,12,13,14,15,16,17,18]. Therefore, this research defines a biowall as a living wall consisting of certain plants with specific substrates in a container assembled on a vertical wall [19] in the interior of a landed housing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are several nomenclatures to explain biowall terminology and these include vertical gardens [5], active living walls [6], and green walls [7,8,9,10,11,12,13,14,15,16,17,18]. Therefore, this research defines a biowall as a living wall consisting of certain plants with specific substrates in a container assembled on a vertical wall [19] in the interior of a landed housing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The author(s) disclosed receipt of the following financial support for the research, authorship, and/or publication of this article: This research was supported in part by the Natural Science Foundation of Zhejiang Province under grant number LQ18E080003. 74 In situ measurement Sound pressure level Indoor Technical Ding et al 50 Lab measurement Absorption coefficient Not specified Technical Horoshenkov et al 14 Lab measurement Absorption coefficient Not specified Technical Renterghem et al 44 Numerical simulation Insertion loss Outdoor Technical Yang et al 33 Lab measurement Absorption coefficient Not specified Technical Kim et al 71 In 53 In situ measurement Absorption coefficient Not specified Technical Paull et al 60 In situ measurement Sound pressure level Outdoor Technical Zhu et al 54 Lab measurement Absorption coefficient Not specified Technical Attal et al 57 Lab…”
Section: Data Availabilitymentioning
confidence: 99%
“…Researchers also use reflection coefficient, transmission coefficient, and sound reduction index to evaluate the acoustic performance of green walls. Attal et al 57 employed the three microphones two-load method developed by Salissou et al 58 to experimentally characterize components of green wall structures and evaluated the corresponding reflection and transmission coefficients. The simulation results demonstrated that the presence of the foliage layer superimposed to the substrate layer does not affect the transmission loss but increases the return loss of the green wall structure.…”
Section: Acoustic Application Of Green Wallsmentioning
confidence: 99%
“…Numerical simulations were also conducted to evaluate how propagation of traffic noise was affected by building enveloppe greening for different urban configurations [7,8]. Laboratory experiments have shown that the main contribution of this absorption comes from the substrate with a clear dependence to substrate composition [5,9,10,11], geometry [5,11,12,13] and moisture content [5,9,12].…”
Section: Introductionmentioning
confidence: 99%